2020
DOI: 10.1037/lat0000153
|View full text |Cite
|
Sign up to set email alerts
|

Family separation and parent–child relationships among Latinx immigrant youth.

Abstract: During the migration process, Latinx immigrant youth often experience prolonged periods of separation from their families for a range of reasons. Family separation can have numerous harmful effects on children’s well-being, but little is known about how separation might affect the quality of the parent–child relationship, an important protective factor, particularly for adolescents. This study examined the relationship between immigration-related family separation and the quality of the parent–child relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Reports of children reunifying with their parents after the family separation policy officially ended in 2018 documented similar responses: many children were withdrawn and disoriented, screamed and cried, or did not recognize their parents (Jordan, Benner, Nixon, & Dickerson, 2018). The effects of interrupted attachment may be lasting; a recent study found that, controlling for covariates, Latinx adolescents who had ever experienced immigration‐related parental separation were significantly more likely to report poor relationship quality with the parent from whom they had been separated (Conway, Roy, Choque, & Lewin, 2020).…”
Section: Research On the Impact Of Immigrant Detention And Family Sepmentioning
confidence: 99%
“…Reports of children reunifying with their parents after the family separation policy officially ended in 2018 documented similar responses: many children were withdrawn and disoriented, screamed and cried, or did not recognize their parents (Jordan, Benner, Nixon, & Dickerson, 2018). The effects of interrupted attachment may be lasting; a recent study found that, controlling for covariates, Latinx adolescents who had ever experienced immigration‐related parental separation were significantly more likely to report poor relationship quality with the parent from whom they had been separated (Conway, Roy, Choque, & Lewin, 2020).…”
Section: Research On the Impact Of Immigrant Detention And Family Sepmentioning
confidence: 99%
“…Women who have made the choice to separate from their families of origin, and particularly from their children, have been found to exhibit depressive symptoms and ambivalence associated with their decision (McGuire & Martin, 2007; Miranda et al, 2005). The length of the separation is often underestimated at the outset, and mother–child ties are strained as children are left with other caregivers, form new attachments, and grow up grieving their absent parent (Conway et al, 2020). Regardless of the circumstances surrounding the migration, it is not uncommon for children and adolescents to experience negative feelings associated with the separation from their caregivers and be at increased risk for depression, anxiety, and behavioral problems (Conway et al, 2020; Mitrani et al, 2004).…”
Section: Valor Definedmentioning
confidence: 99%
“…The length of the separation is often underestimated at the outset, and mother–child ties are strained as children are left with other caregivers, form new attachments, and grow up grieving their absent parent (Conway et al, 2020). Regardless of the circumstances surrounding the migration, it is not uncommon for children and adolescents to experience negative feelings associated with the separation from their caregivers and be at increased risk for depression, anxiety, and behavioral problems (Conway et al, 2020; Mitrani et al, 2004). Findings from a study of Latinx immigrant youth (84% of the sample from El Salvador, Guatemala, and Honduras) revealed that immigrant adolescents with experiences of migration-related parent separations were more likely to report poor relationships with their mothers and fathers (Conway et al, 2020).…”
Section: Valor Definedmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, they may be temporarily left behind by one or more parents with the expectation of reuniting later in the United States (Smith, Lalonde, & Johnson, 2004). In most cases, the UAMs will be cared for by a surrogate caregiver and may spend many years with them prior to reuniting with parents (Conway et al, 2020). After entering the United States, immigrant youth may also experience an involuntary separation from parents or other relatives who were their travel companions, as a result of government detainment practices (Dreby, 2015).…”
Section: Introductionmentioning
confidence: 99%